SAT0028 THE FLARE-RA QUESTIONNAIRE CAN PREDICT FLARES IN PATIENTS WITH ESTABLISHED RHEUMATOID ARTHRITIS PARTICIPATING IN THE TAPERA TRIAL. (13th June 2020) - Bertrand, D.; De Cock, D.; Stouten, V.; Pazmino, S.; Moeyersoons, A.; Joly, J.; Westhovens, R.; Verschueren, P.
Abstract : Background: The Flare assessment in Rheumatoid Arthritis (FLARE-RA) questionnaire was developed to identify Rheumatoid Arthritis (RA) flares, but it is unknown if this questionnaire can also predict flares. Objectives: To identify if the FLARE-RA questionnaire has a predictive capacity for OMERACT flares in patients with established RA participating in a tapering trial. Methods: Patients, participating in the 1-year open-label pragmatic randomised controlled TapERA (Tapering Etanercept in RA) trial, were included in the analysis. Patients had to be in DAS28CRP or ESR remission (≥6 months) and treated with etanercept 50 mg weekly (≥1 year). Participants were randomised to continue etanercept 50 mg weekly or to taper to 50 mg every other week. The FLARE-RA questionnaire was completed every 3 months in the trial. This questionnaire consists of 13 questions on a Likert-scale from 1 to 6 reflecting 'completely untrue' to 'completely true'. Validation by Fautrel et al. leaded to elimination of 2 questions ('steroid intake' and 'overall worsening of RA') and rescaling to 0-10. Our outcomes were based on these 3 versions of the questionnaire, namely 13 questions (13q), 11 questions (11q) and rescaled 11 questions (r11q). The FLARE-RA questionnaire can be divided in 2 subscales: the FLARE-RA arthritis subscale (questions regarding morning stiffness, night disturbances, joint swelling, joint pain, analgesics) and FLARE-RA general symptoms subscale (questions regarding fatigue, functional limitation, irritability, mood disturbances, withdrawal, need for help). The total FLARE-RA score was calculated by taking the average of all the questions per time point. A flare was defined according to the OMERACT definition, namely an increase in DAS28CRP > 1.2 compared to baseline or increase in DAS28CRP > 0.6 and current DAS28CRP ≥ 3.2. All the total FLARE-RA scores of the baseline, month 3, 6 and 9 visit were grouped and the mean ± standard deviation (SD) FLARE-RA score was compared between patients with or without an OMERACT flare on the next study visit using the Mann-Whitney U test. Logistic regressions using the total FLARE-RA score to predict an OMERACT flare 3 months later were carried out for the 13q, 11q and r11q versions and the FLARE-RA subscales. Missing data were imputed using expectation maximisation. Results: Sixty-six patients (68% female, mean ± SD age of 55 ± 11 years) completed the FLARE-RA questionnaire. This yielded 264 FLARE-RA scores, of which the total mean ± SD FLARE-RA score was 2.1 ± 1.0 and 2.7 ± 1.1 for patients without and with an OMERACT flare on the next study visit, respectively (p<0.01). This was comparable for the 11q and r11q versions (Table 1 ). For the total FLARE-RA score (13q), the odds ratio of having an OMERACT flare 3 months later is 1.6 (95% confidence interval (CI) 1.2 – 2.2, p=0.004). This was 1.5 (95% CI 1.1 – 2.1, p=0.006) for the 11q and 1.2 (95% CI 1.1 – 1.4, p=0.006) for the r11q version. The odds ratio of having an OMERACT flare on the next visit was 1.5 (95% CI 1.2 – 2.0, p=0.002) and 1.4 (95% CI 1.0 – 2.0, p=0.025) for the arthritis and general symptoms subscale, respectively. Conclusion: Higher total FLARE-RA questionnaire scores seem to indicate a higher risk of an OMERACT flare 3 months later, regardless of which versions or subscales of the FLARE-RA questionnaire were used. Hence, our findings suggest that the FLARE-RA questionnaire could be used as a predictive tool for flares. Disclosure of Interests: Delphine Bertrand: None declared, Diederik De Cock: None declared, Veerle Stouten: None declared, Sofia Pazmino: None declared, Anneleen Moeyersoons: None declared, Johan Joly: None declared, Rene Westhovens Grant/research support from: Celltrion Inc, Galapagos, Gilead, Consultant of: Celltrion Inc, Galapagos, Gilead, Speakers bureau: Celltrion Inc, Galapagos, Gilead, Patrick Verschueren Grant/research support from: Pfizer unrestricted chair of early RA research, Speakers bureau: various companies